Factors associated with contracting border malaria: A systematic and meta-analysis - Tichaona Fambirai; Moses Chimbari; Tafadzwa Mhindu (PLoS ONE, 2025)
Vector resistance, human population movement, and cross-border malaria continue to pose a threat to the attainment of malaria elimination goals. Border malaria is prominent in border regions characterised by poor access to health services, remoteness, and vector abundance. Human socio-economic behaviour, vectoral behaviour, access and use of protective methods, age, sex, and occupation have been identified in non-border regions as key predictors for malaria. We conducted a systematic and meta-analysis review to characterise and establish pooled effect sizes of the factors associated with the occurrence of border malaria. An exhaustive search was done in EBSCOHost (Medline Full Text), Health Source, Google Scholar, Regional Office for Africa Library, African Index Medicus, and PubMed databases. A total of 847 articles were identified from the search and after screening for quality and eligibility, twelve (12) articles were included in the review. Pooled odds ratios, inverse variance statistic (I2), Luis Furuya-Kanamori (LFK) index, and forest plot were computed. Findings from this study suggest night outdoor activities (POR 2.87 95% CI, 1.17 7,01), engaging in forestry activities (POR 2.76 95% CI, 2.08 3.67), working in mines (POR 197 95% CI, 175 22171), access to poor housing structure (POR 3.42 95% CI, 2.14 5.46), and cross-border movement (POR 50.86 95% CI, 12.88 200.85) none use of insecticide-treated nets (POR 5.09 95% CI, 2.44 10.63) were all significantly associated with contracting malaria within border regions. The use of insecticide-treated nets (ITN) (POR 0.61 95% CI, 0.50 0.76) and indoor residual spraying (IRS) (POR 0.61 95% CI, 0.47 0.79) were protective. Risk factors for border malaria are comparable to non-border malaria. Effective border malaria control requires an integrated and targeted approach that addresses socio-economic, environmental, and behavioural drivers. Established vector control interventions remain protective and should be sustained to mitigate the border malaria burden effectively. Novel strategies should be developed to address the unique challenge of cross-border human population movement underpinned by robust regional, bilateral, and multi-sectoral collaborative initiatives.